2018
DOI: 10.1186/s12920-018-0446-7
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the landscape of tandem repeat variability by targeted long read single molecule sequencing in familial X-linked intellectual disability

Abstract: BackgroundThe etiology of more than half of all patients with X-linked intellectual disability remains elusive, despite array-based comparative genomic hybridization, whole exome or genome sequencing. Since short read massive parallel sequencing approaches do not allow the detection of larger tandem repeat expansions, we hypothesized that such expansions could be a hidden cause of X-linked intellectual disability.MethodsWe selectively captured over 1800 tandem repeats on the X chromosome and characterized them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…However, emerging long-read sequencing (LRS) technologies, typified by PacBio single-molecule and real-time (SMRT) sequencing, offer complementary strengths to those of the SRS methods and are well suited to determine expanded tract length and variation in repeat numbers [ 76 ]. Applied to Fragile-X diagnosis, LRS technology enabled researchers to completely sequence expanded full mutation FMR1 alleles, with up to 750 CGG repeats, which translates to >2 kb of 100% CGG-repeat DNA [ 77 , 78 ]. In DM1 patients, LRS sequencing detected de novo repeat interruptions at the DMPK locus, associated with the reduced somatic instability of the repeat expansion [ 79 ].…”
Section: Diagnostic Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, emerging long-read sequencing (LRS) technologies, typified by PacBio single-molecule and real-time (SMRT) sequencing, offer complementary strengths to those of the SRS methods and are well suited to determine expanded tract length and variation in repeat numbers [ 76 ]. Applied to Fragile-X diagnosis, LRS technology enabled researchers to completely sequence expanded full mutation FMR1 alleles, with up to 750 CGG repeats, which translates to >2 kb of 100% CGG-repeat DNA [ 77 , 78 ]. In DM1 patients, LRS sequencing detected de novo repeat interruptions at the DMPK locus, associated with the reduced somatic instability of the repeat expansion [ 79 ].…”
Section: Diagnostic Toolsmentioning
confidence: 99%
“…In addition, a genome-wide DNA methylation assay has been successfully applied to the molecular diagnosis of genetically unresolved cases, uncovering new hypervariable trinucleotide repeat loci [ 72 , 83 ]. Collectively, emerging Next-Generation Sequencing (NGS) technologies offer efficient strategies in the characterization of expandable regions that are difficult to assess with NGS short-read approaches and, thus, we believe that novel hypermethylated expansion disorders could be identified in the future [ 72 , 76 , 78 ]. Fascinatingly, these new technologies could lead a new field of studies to trace DNA methylation in repeat ancestors by comparing ancient and modern human genomes and highlighting epigenetic differences at disease repeat loci.…”
Section: Diagnostic Toolsmentioning
confidence: 99%
“…Genes including SHROOM3, FCER1A, DLEC1, and PSAPL1 are shown to be targeted by miR-145; genes ROBO2, CHAF1B, P2RY22, XRRA1, GPX8, P2RY2, and NSG1 are targeted by miR-183 [33]. Genes ARMCX2, NEFH, and FMR1 are shown to be targeted by miR-222 [37]. The gene MECP2, which is related to IDs such as Rett Syndrome can be targeted by miR-302c, miR-483-5p, miR-130a, and miR-200a.…”
Section: Mirna-gene Pair Selection Screenmentioning
confidence: 96%
“…Though there are several widely accepted miRNA targeting databases available, in order to obtain ID-related miRNA-mRNA pairings, we collected known and predicted pairs of miRNA and target genes from published literatures. After extensive research about known miRNA and mRNA targeting relationships, we obtained a list of miRNA-mRNA pairs from nine published literatures [24,[32][33][34][35][36][37]. The list of miRNA-mRNA pairs selected for this study is reported in Table S1.…”
Section: Input Data Curation From Literaturementioning
confidence: 99%